2020
DOI: 10.1186/s12889-020-8310-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal BMI, breastfeeding practices and infant anthropometric status in Colombia; secondary analysis of ENSIN 2010

Abstract: Background: Maternal malnutrition and infant feeding mode impact short and long term infant and child morbidity and mortality. The period of lactation may provide an opportunity to modulate the risk of disease later in life. Our aim was to estimate the effect of maternal body mass index (BMI) and infant feeding mode, particularly breastfeeding practices, on the anthropometric status of children under 2 years in Colombia. Methods: A secondary analysis was performed using the data from ENSIN 2010. Term infants u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In Aldana-Parra et al . [ 15 ] study, wealth index did not have significant association with wasting in children ( P value 0.12)…”
Section: Determinants Of Health Statusmentioning
confidence: 89%
“…In Aldana-Parra et al . [ 15 ] study, wealth index did not have significant association with wasting in children ( P value 0.12)…”
Section: Determinants Of Health Statusmentioning
confidence: 89%
“…In our study, maternal height was significantly associated with stunting in children. Studies in Indonesia, and of African and Latin American countries such as Malawi, Rwanda, and Colombia, have reported that maternal height was related to stunting (Aldana-Parra et al, 2020;Nshimyiryo et al, 2019;Rachmi et al, 2016;Walters et al, 2019). In addition, a study conducted in Vietnam showed that maternal height had a strong association with child stunting (Beal et al, 2019).…”
Section: Discussionmentioning
confidence: 99%